Analysis of Genetic Variation among Different Banana Cultivars - Vignesh, H.; Hema Kalai Rani, R. (Asian Journal of Science and Applied Technology, 2012)
The banana (Musa spp.) is considered as an important crop plant due to its high economic value as good dietary source. Banana is the rich source of carbohydrates and vitamins, particularly vitamins B; it is also a good source of potassium, phosphorus, calcium and magnesium. Here, we analyzed the genetic relationship of four different banana varieties that are cultivated in south India. Random amplified polymorphic DNAs (RAPDs) fingerprinting of these banana varieties (Grand Naine, Nendran, Poovan and Red Banana) were carried out by five decamer primers (OP-5, OP-6, OP-7, OP-8,OP-11) led to DNA amplification. The distances in the dendrogram constructed by UPGMA (Unweighted pair group method Arithmetical Means) were compared with the genetic distances between genotypes pairs to calculate the cophenetic correlation. The genetic variation between Grand naine and Nendran was found to be 0.89 nucleotide. Similarly the Poovan is getting 0.94 nucleotide variation from the above one and Red is getting 0.97 nucleotide at the highest from all. The results presented here also contribute to narrowing the gaps in our current understanding of the migration path of bananas and the emergence of secondary centers of diversity. Cultivated bananas (Musa spp.) are mostly diploid or triploid cultivars with various combinations of the A and B genomes inherited from their diploid ancestors Musa acuminata Colla. and Musa balbisiana Colla. respectively.